2014
DOI: 10.1016/j.jlumin.2014.02.039
|View full text |Cite
|
Sign up to set email alerts
|

VUV–UV 5d–4f interconfigurational transitions of Nd3+ in BaMgF4 ferroelectric crystals

Abstract: a b s t r a c tBaMgF 4 single crystals doped with Nd 3 þ are of great interest as possible active media for VUV-UV and mid-IR all solid-state lasers. The luminescence spectroscopy and the excited state dynamics of these crystals are investigated for the first time upon VUV excitation using synchrotron radiation. The material shows fast Nd 3 þ 5d-4f emission upon direct VUV excitation into Nd 3 þ 5d levels. The decay kinetics of the Nd 3 þ 5d-4f emission in this host lattice upon direct VUV excitation of 5d lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…5 Thus BMF crystals have been studied as new solid-state laser materials in the UV region. [6][7][8][9][10][11] These properties make BMF a good candidate for integrated optical devices. Although the pure compound doesn't exhibit ferromagnetism, it has been recently demonstrated that this property can be induced by substitutional doping of Mg by a magnetic transition metal ion such as Mn.…”
Section: Introductionmentioning
confidence: 99%
“…5 Thus BMF crystals have been studied as new solid-state laser materials in the UV region. [6][7][8][9][10][11] These properties make BMF a good candidate for integrated optical devices. Although the pure compound doesn't exhibit ferromagnetism, it has been recently demonstrated that this property can be induced by substitutional doping of Mg by a magnetic transition metal ion such as Mn.…”
Section: Introductionmentioning
confidence: 99%